Employment of an Extended Double-Integrating-Sphere System to Investigate Thermo-optical Material Properties for Powder Bed Fusion - Schuffenhauer, Thomas; Stichel, Thomas; Schmidt, Michael (Journal of Materials Engineering and Performance, 2021)
The optical energy input during laser-based powder bed fusion of polymers (PBF-LB/P) is influenced by a variety of process parameters (e.g., energy density) and powder material properties (e.g. optical properties, additives). Qualification of newly developed and/or modified powder materials still requires extensive, empirical parameter studies to assess processibility and find suitable process strategies. For powder characterization, a double-integrating-sphere system with an intervening hot stage, which allows accurate sample heating during the measurement of the optical properties, is presented and described. For qualification of the system and the associated characterization method for the PBF-LB/P process, the interaction of a collimated CO2 laser beam with selected polyamide powder materials during heating and cooling is investigated. The obtained results illustrate the suitability of the presented thermo-optical characterization technique, i.e., the temperature-dependent measurement of radiation reflected by and transmitted through the samples, for the systematical investigation of material-related (i.e., additives) and process-related (i.e., preheating temperature, layer height) influences on the beam-matter interaction.
CRIS-Team Scopus Importer:2021-03-19
Keywords: integrating sphere; material characterization; optical properties; polymer; powder bed fusion